Repercussion of the COVID-19 pandemic on the lives and work of ICU nursing technicians - Katia Maria Rosa Vieira; Francisco Ubaldo Vieira Junior; Zélia Zilda Lourenço de Camargo Bittencourt (Universidade Federal do Rio Grande do Sul, 2023)
ABSTRACT Objective: To investigate the impact of the COVID-19 pandemic on personal dimensions and its relationship with the work context of nursing technicians who worked in ICUs. Method: A cross-sectional mixed-method study (convergent parallel). A total of 229 nursing technicians from intensive care units participated and responded a questionnaire. The study was conducted using the IRaMuTeQ software for lexicographic verification and similarity analysis of the corpus and the Minitab 19 software for comparison between means and logistic regression. Results: Fear was found that the biggest impact on the lives of nursing technicians. The professionals experienced stress and anxiety as a consequence of the fear of Coronavirus infection and its transmission to their families. Conclusion: The pandemic affected the daily personal lives of nursing technicians, in the same work context, in different ways.